THE EFFECT OF PRINCIPALS’ LEARDHERSHIP STYLES ON TEACHERS’ PERFOMANCE AT PUBLIC ELEMENTARY SCHOOLS IN KECAMATAN SOROMANDI, BIMA DISTRICT - Ikang Susmita; Muhammad Basri; Muhammad Nawir (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to determine the effect of principals’ leadership style on the teachers’ performance at public elementary schools in Kecamatan Soromandi, Kabupaten Bima. The research utilized a quantitative approach. The population in this study were 128 elementary school teachers in Kecamatan Soromandi, Kabupaten Bima. From the population, 50 teachers were taken as the samples by using probability sampling techniques. The data were collectedthrough a questionnaire. The assumption test was the normality and linearity test while the hypotheses were examined by using simple regression analysis. The results of this study concluded that the Leadership Style Dominantly Performed by Principals at Public Elementary Schools in Kecamatan Soromandi, Kabupaten Bima was Democratic Leadership Style with a score of 67.43%, in a strong correlation and Transactional Leadership Style was in a low correlation with a score of 32.57%. Meanwhile, the teachers’ performance at public elementary schools in Kecamatan Soromandi, Kabupaten Bima was in a strong correlation with a score of 60.54%. Furthermore, the Principals’ Leadership Style Affected the Teachers’ Performance at Public Elementary Schools in Kecamatan Soromandi, Kabupaten Bima which was shown by a value of 63.90% with a significance of 0.00 <0.05. The score of the influence of principals’ leadership style on teachers’ performance was 63.90% and was strongly correlated.